Mavericks, Universal, and Common Owners - The Largest Shareholders of U.S. Public Firms - Amir Amel-Zadeh; Fiona Kasperk; Martin C. Schmalz (Center for Economic Studies and ifo Institute (CESifo), 2022)
We construct a novel data set to show that, between 2003-2020, up to one-fifth of America's largest firms had a non-financial blockholder or insider as their largest shareholder. Blockholders and insiders tend to be less diversified than institutional investors. Measures of "universal" and "common" ownership of firms are therefore lower than previously believed based on analyses of institutional investors' holdings alone, and the heterogeneity in ownership structures across firms is greater. Consolidation in the asset management industry increases universal ownership and common ownership of industry rivals. Extant results claiming indexing alone explains the rise of universal ownership cannot be confirmed with the new, more comprehensive data.
Keywords: G23; G34; L21; L40; 330; common ownership; institutional ownership; blockholders; insiders; antitrust; governance